Aptian giant explosive volcanic eruptions in the Songliao Basin and northeast Asia: A possible cause for global climate change and OAE-1a. (July 2016) - Wang, Pujun; Chen, Chongyang; Liu, Haibo
Abstract: Volcanism is a natural climate force that causes variations in temperatures. The Aptian Oceanic Anoxic Event 1a (OAE-1a) was preceded by a prominent negative C-isotope excursion attributed to major volcanism of the Ontong Java plateau (OJP), which presumably resulted in a pCO2 increase and a climatic change. However, the OJP alone may not adequately explain some important isotopic signatures such as the negative strontium-isotope excursion from 125 Ma to 113 Ma that is recorded in the corresponding marine deposits. We present an independent and hitherto undocumented case, the giant Aptian volcanism in the Songliao Basin and northeast Asia (SB-V) on the Cretaceous active continental margin between the Eurasian and the Pacific plates, which covered an area of ca. 2.3 × 10 6  km 2, nearly matching the simultaneous case of the OJP. Intensive strong, explosive volcanic eruptions of the SB-V occurred at 121–109 Ma and introduced a large volume of fine-grained volcanic ash and degassing volatiles into the atmosphere. The Aptian isotopic ratios ( 87 Sr/ 86 Sr, 206 Pb/ 204 Pb, 207 Pb/ 204 Pb, and 208 Pb/ 204 Pb) of marine carbonates from the Mid-Pacific shift in values between their Barremian pre-excursion high values and the negative magmatic values of the SB-V. The transient global cooling at the onset of the OAE-1a coincided with the beginning of the violent acidic eruption of the SB-V (119.9–120.2 Ma). We therefore infer that the SB-V must have played a role in the Aptian global climatic changes and OAE-1a through the heavy fall of volcanic dust and the outgassing of aerosol and greenhouse gases. Highlights: Aptian volcanism in the Songliao Basin & NE Asia (SB-V) can mach that of the OJP. The SB-V mega-eruptions started at the same time with the onset of the OAE-1a. The SB-V explosive eruption ash fall impacted on isotopes of the marine deposits. The SB-V outgassing gases had contributed to the global climate change and OAE-1a.